Resting State EEG Directed Functional Connectivity Unveils Changes in Motor Network Organization in Subacute Stroke Patients After Rehabilitation - Pirovano, Ileana; Mastropietro, Alfonso; Antonacci, Yuri; Barà, Chiara; Guanziroli, Eleonora; Molteni, Franco; Faes, Luca; Rizzo, Giovanna (Frontiers in Physiology, 2022)
Brain plasticity and functional reorganization are mechanisms underpinning motor recovery after an ischemic stroke. Assessing resting-state motor network functional connectivity through EEG proved to be useful in investigating changes occurring in the information flow and finding correlation with motor function recovery. In literature, most studies applying EEG to post-stroke patients focused on undirected functional connectivity between brain regions. Recently, works started to investigate the directionality of the connections many approaches have been proposed, each of them being more suitable to describe different aspects, e.g., direct or indirect information flow between nodes, the coupling strength or its characteristic oscillation frequency. Currently, the selection of the most appropriate metric is still an open issue. Attempting to shed light on this methodological aspect, we propose here to combine the information of direct and indirect coupling using two metrics based on Granger’s causality, i.e., the directed coherence (DC) and the generalized partial directed coherence (gPDC). The proposed approaches were used to evaluate the longitudinal changes of resting-state directed connectivity, in α and β bands, occurring in 18 sub-acute ischemic stroke patients who followed a rehabilitation treatment. Our results showed a relevant role of the information flow through the pre-motor regions in the reorganization of the motor network after the rehabilitation. In particular, DC highlighted an increase in intra-hemispheric coupling strength between pre-motor and primary motor areas, especially in ipsi-lesional hemisphere in both α and β frequency bands, whereas gPDC was more sensitive in the detection of those connection whose variation was mostly represented within the population. A decreased causal flow from contra-lesional premotor cortex towards supplementary motor area was detected in both α and β bands and a significant reinforced inter-hemispheric connection from ipsi to contra-lesional pre-motor cortex was observed in β frequency. Interestingly, the connection from contra towards ipsilesional pre-motor area correlated with upper limb motor recovery in α band. Using two different measures of directed connectivity allowed a better comprehension of those coupling changes between brain motor regions, either direct or mediated, which mostly were influenced by the rehabilitation, revealing a particular involvement of the pre-motor areas in the cerebral functional reorganization.